Pelaksanaan Perjanjian Pinjaman Yang Memuat Klausula Baku Pada Koperasi Simpan Pinjam Bersinar Pesanggaran - I Made Sara; I Wayan Kartika Jaya Utama; A.A.Media Martadiani; Ni Putu Riasning; Ni Gusti Agung Ayu Wulan Ananda Pratiwi; I Made Abdi Nassa Jayantara; I Kadek Darmawan (Postgraduated Community Service Journal, 2024)
The Bersinar Pesanggaran Savings and Loan Cooperative (KSP) is located in Pedungan Village, South Denpasar District, Denpasar City which is engaged in banking. The development of credit at KSP Bersinar Pesanggaran has increased not so significantly from 2021-2023, while the number of non-performing loans has increased a lot in 2021 to 2023. Service at KSP Bersinar Pesanggaran begins by conducting observations and interviews with the Cooperative Management by using socialization, training and mentoring methods to employees regarding good credit receipt procedures in accordance with applicable procedures and provisions in order to avoid non-performing loans not increasing in the future in order to overcome the problems faced by partners. In its implementation, it was explained the classification of the collectibility status of banking loans in accordance with Financial Services Authority Regulation Number 40/POJK.03/2019 and to handle non-performing loans can be done through prevention, handling and backup methods. The expected end result of this activity is to help partners in preventing and avoiding the increase in non-performing loans.